A QUALITATIVE STUDY INQUIRING PERCEIVED STIGMA OF PARENTS HAVING CHILDREN WITH AUTISM ATTENDING A REHABILITATION CENTER IN ISTANBUL, TURKEY - (:unkn) unknown (NOBEL ILAC, 2020)
Objective: Decreasing discrimination and stigmatization, creating a sense of responsibility among citizens on children and their families and increasing public awareness towards children having autism can be very important in the early diagnosis and treatment of autism since the most important treatments of autism can be accomplished in social settings. The aim of this qualitative study, carried out in Istanbul was to evaluate the perceptions of social stigma of a group of parents who have children with autism. Material and Method: In this qualitative study, data was collected via in-depth interviews with ten parents who have children with autism. Thematic content analysis was used subjective interpretation of textual data through the process of coding and the identification of themes. Results: Five themes were identified: 1) Stigmatization in the big family; 2) stigmatization in the community; 3) stigmatization in school/preschool period; 4) stigmatization in healthcare settings; and 5) coping with stigmatization. The community does not only label the child having autism but also his family members. It has been determined that one of the main problems in relation to teaching children with autism is that mainstream schools do not accept children with autism on excuses of various reasons. Conclusion: The parents of children with autism experienced exclusion, discrimination and stigmatization both in the families and in the community. Children were mostly discriminated during school period. Stigmatization existed not only by the community but also in the healthcare settings. To this end, parents felt isolated in the community.
Keywords: Qualitative research; stigmatization; autism; discrimination; SPECTRUM DISORDER; KNOWLEDGE; EXPERIENCES; ATTITUDES; DIAGNOSIS; EDUCATION